2R-Regeneration of an 80-Gb/s RZ-DQPSK signal by a nonlinear amplifying loop mirror - Cvecek, Kristian; Sponsel, Klaus; Ludwig, R.; Schubert, C.; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R-regenerator for an 80-Gb/s return-to-zero differential-quadrature-phase-shift-keyed signal has been investigated experimentally. A significant eye-opening improvement and a negative power penalty of up to 2.6 dB were obtained. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.2rrege
Keywords: 2R-regeneration; All-optical regeneration; Differential quadrature phase-shift keying (DQPSK); Nonlinear amplifying loop mirror (NALM)

8 QAM regeneration using a phase-sensitive amplifier with dual-conjugated pumps - Stiller, Birgit; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
CRIS-Team Scopus Importer:2021-06-29

All-Optical Multilevel Amplitude and Phase Regeneration - Röthlingshöfer, Tobias; Richter, T.; Onishchukov, Georgy; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (2014 IEEE Photonics Society Summer Topical Meeting Series, 2014)
Using a cascade of an amplitude and a phase regenerator, multilevel signal processing is demonstrated experimentally for a 25-GBd star-8QAM. Improvements in the signal quality by up to 2 dB are obtaine
lhft_intern.bib::Roethlingshoefer2014_6

All-optical phase-preserving multilevel amplitude regeneration - Röthlingshöfer, Tobias; Richter, Thomas; Schubert, Colja; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
The possibility of all-optical phase-preserving amplitude regeneration for star-8QAM is demonstrated using a modified nonlinear optical loop mirror. Experiments show a reduction in amplitude noise on both amplitude levels simultaneously, considering two different types of signal distortions: deterministic low-frequency amplitude modulation and broadband amplitude noise. Furthermore, using this amplitude regeneration, the robustness against nonlinear phase noise from fiber nonlinearity in a transmission line is increased. The scheme suppresses the conversion of amplitude noise to nonlinear phase noise. This is shown for simultaneous amplitude regeneration of the two amplitude states as well as for amplitude regeneration of the high-power states only. If the transmission is limited by nonlinear phase noise, single-level operation at the more critical higher-power state will benefit because of the wider plateau region. Numerical simulations confirm the experimental result

All-optical signal regeneration of advanced modulation formats - Röthlingshöfer, Tobias; Richter, Thomas; Stiller, Birgit; Onishchukov, Georgy; Schubert, Colja; Schmauß, Bernhard; Leuchs, Gerd (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIII, 2014)
With growing demand on transmission capacity, spectral-efficient multilevel modulation formats such as quadrature amplitude modulation (QAM) become of great interest. One of their weaknesses is high sensitivity to noise accumulation, especially in long-haul transmission systems. Our investigations have shown the possibility of all-optical regeneration of multiple amplitude and phase states. Processing of amplitude noise in several amplitude states is based on periodicity of interference conditions in modified nonlinear fiber Sagnac interferometers. Their staircase-like power transfer characteristic can be used for phase-preserving amplitude regeneration of multiple amplitude states. Processing of QAM with up to three non-zero amplitude states, e.g. 16QAM, has been demonstrated in numerical simulations. Furthermore, simultaneous amplitude regeneration of a star-8QAM format with two amplitude states was performed experimentally. Recently, it has also been shown that phase-sensitive amplification for multiple phase states can be realized in fiber optical parametric amplifiers using four-wave mixing (FWM) with a high-order idler. Our numerical simulations and experimental results for star-8QAM revealed that with some modifications, this approach can be used not only for reduction of phase noise in multilevel phase-shift keying but also for signals with multiple amplitude states. The transmission improvement using a cascade of these two regenerator types has been demonstrated in numerical simulations and experiments. Numerical investigations confirm also the possibility to combine both approaches in a single device by using the highly nonlinear fiber in the Sagnac interferometer loop simultaneously for phase-sensitive amplification in one propagation direction. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Roethlingshoefer2014_8

All-Optical Simultaneous Multilevel Amplitude and Phase Regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2014)
Simultaneous amplitude and phase noise reduction of multiple signal states using a nonlinear amplifying loop mirror with integrated directional phase-sensitive amplifier are presented for the star-eight quadrature amplitude modulation transmission format as an example. The performance of this combined regenerator scheme is compared with that of a cascade of separate phase and amplitude regenerators. It could be shown that an improvement in the error vector magnitude of 4 dB for the high-power states with simultaneous improvement of 5 dB for the low-power states is possible in both cases. Transmission improvement by regeneration is considered for two noise types: 1) amplified spontaneous emission and 2) nonlinear phase noise. Both schemes can either improve the bit error rate by an order of magnitude or enable an increase of the fiber launch power by 3 d
lhft_intern.bib::Roethlingshoefer2014a

Amplitude noise reduction in multilevel QAM formats using a nonlinear amplifying loop mirror with a saturable amplifier - Roethlingshoefer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics Europe (CLEO EUROPE/EQEC), 2011 Conference on and 12th European Quantum Electronics Conference, 2011)
lhft_intern.bib::Roethlingshoefer2011

A multiwavelength emission detector for analytical ultracentrifugation - Wawra, Simon; Onishchukov, Georgy; Maranska, Maria; Eigler, Siegfried; Walter, Johannes; Peukert, Wolfgang (Nanoscale Advances, 2019)

Cascaded Phase-Preserving Amplitude Regeneration in a DPSK Transmission System - Schmauß, Bernhard; Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Leuchs, Gerd (ECOC 2009, Vienna, Austria, 20-24 September, 2009)
Experimental results obtained on 10 Gb/s RZ-DPSK transmission in a recirculating fiber-loop setup show that nonlinear amplifying loop mirrors can efficiently enhance system performance. Main limiting factor is amplified Rayleigh backscattering in highly nonlinear fiber. © VDE VERLAG GMBH.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.cascad

Cascaded phase-preserving multilevel amplitude regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
The performance of cascaded in-line phase-preserving amplitude regeneration using nonlinear amplifying loop mirrors has been studied in numerical simulations. As an example of a spectrally efficient modulation format with two amplitude states and multiple phase states, the regeneration performance of a star-16QAM format, basically an 8PSK format with two amplitude levels, was evaluated. An increased robustness against amplified spontaneous emission and nonlinear phase noise was observed resulting in a significantly increased transmission distance.
lhft_intern.bib::Roethlingshoefer2014_4

Compensation of Nonlinear Phase Noise Using the Effective Negative Nonlinearity of a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Journal of Selected Topics in Quantum Electronics, 2012)
The nonlinear amplifying loop mirror (NALM) has been explored for use as a nonlinear phase-shift compensator (NPSC). Operation conditions for a tunable effective negative nonlinearity are considered and the NALM parameter optimization is discussed for direct bit-error-ratio (BER) improvement by postcompensation after a nonlinear transmission line. In this configuration, the fundamental limits for NPSC are estimated for differential quadrature phase-shift keying (DQPSK) using a simplified model. Numerical simulations of a 20 Gb/s RZ-DQPSK transmission system confirmed the applicability of this model and showed a significant BER improvement in a realistic transmission line. Alternatively, the fiber launch power per span could be increased by 2 dB for the same BE
lhft_intern.bib::Sponsel2012

Development of an advanced multiwavelength emission detector for the analytical ultracentrifuge - Lautenbach, Vanessa; Onishchukov, Georgy; Wawra, Simon; Frank, Uwe; Hartmann, Lukas; Peukert, Wolfgang; Walter, Johannes (Nanoscale Advances, 2024)
An advanced design of the analytical ultracentrifuge with multiwavelength emission detection (MWE-AUC) is presented which offers outstanding performance concerning the spectral resolution and range flexibility as well as the quality of the data acquired. The excitation by a 520 nm laser is complemented with a 405 nm laser. An external spectrograph with three switchable tunable gratings permits optimisation of the spectral resolution in an order of magnitude range while keeping the spectral region broad. The new system design leads also to a significant reduction of systematic signal noise and allows the assessment and control of inner filter effects. Details regarding the very large signal dynamic range are presented, an important aspect when studying samples in a broad concentration range of up to five orders of magnitude. Our system is validated by complementary studies on two biological systems, fluorescent BSA and GFP, using the commercial Optima AUC with absorbance detection for comparison. Finally, we demonstrate the capabilities of our second generation MWE-AUC with respect to multiwavelength characterisation of gold nanoclusters, which exhibit specific fluorescence depending on their structure. Overall, this work depicts an important stepping stone for the concept of multiwavelength emission detection in AUC. The MWE-AUC developed, being to our knowledge the first and sole one of its kind, has reached the development level suitable for the future in-depth studies of size-, shape- and composition-dependent emission properties of colloids.
CRIS-Team Scopus Importer:2024-03-22

DPSK Signal Regeneration Using a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Stephan, Christian; Cvecek, Kristian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Conf. Proc. OFC, Paper OThB2, March, 2007)
Power characteristics and phase functions of a NALM are investigated in simulations and experimentally, showing a phase-preserving nonlinear characteristics suitable for amplitude regeneration of phase-encoded signals. A negative power penalty of -1.5 dB was obtained. ©2006 Optical Society of America.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.dpsksi

Effective Negative Nonlinearity of a Nonlinear Amplifying Loop Mirror for Compensating Nonlinearity-Incuced Signal Distortions - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication, 2008. ECOC 2008. 34th European Conference on 21-25, 2008)
UnivIS-Import:2017-12-18:Pub.2008.tech.IE.LEH.effect

Experimental Investigation of a Modified NOLM for Phase-Encoded Signal Regeneration - Cvecek, Kristian; Onishchukov, Georgy; Sponsel, Klaus; Striegler, Arne; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2006)
We experimentally investigate the amplitude and phase transfer characteristics of a modified nonlinear optical loop mirror (NOLM) with a directional attenuator (DA-NOLM) optimized for differential phase-shift keying signal regeneration. The results show that the phase relation is preserved in the setup and thus the DA-NOLM is suitable for amplitude regeneration of phase-shift-keyed signals. © 2006 IEEE.
UnivIS-Import:2015-04-14:Pub.2006.tech.IE.LEH.experi
Keywords: 2R regeneration; All-optical regeneration; Differential phase-shift keying (DPSK); Nonlinear optical loop mirror (NOLM)

Fiber-modes and fiber-anisotropy characterization using low-coherence interferometry - Ma, Y. Z.; Sych, Denis; Onishchukov, Georgy; Ramachandran, S.; Peschel, Ulf; Schmauß, Bernhard; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2009)
An optical low-coherence interferometry technique has been used to simultaneously resolve the mode profile and to measure the intermodal dispersion of guided modes of a few-mode fiber. Measurements are performed using short samples of fiber (about 50 cm). There is no need for a complex mode-conversion technique to reach a high interference visibility. Four LP mode groups of the few-mode fiber are resolved. Experimental results and numerical simulations show that the ellipticity of the fiber core leads to a distinct splitting of the degenerate high-order modes in group index. For the first time, to the best of our knowledge, it has been demonstrated that degenerate LP11 modes are much more sensitive to core shape variations than the fundamental modes and that intermodal dispersion of high-order degenerate modes can be used for characterizing the anisotropy of an optical waveguide.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.optik.1optik.fiberm

Hydrolase and Peroxidase Activity of Gold Nanocluster Composites with Lysozyme and Cross-Linked Lysozyme Crystals - Akyüz, Özlem; Brodhag, Manuel; Lautenbach, Vanessa; Krumova, Marina; Onishchukov, Georgy; Walter, Johannes; Gavira, José Antonio; Cölfen, Helmut (ACS Applied Nano Materials, 2024)
Lysozyme (Lyz) and cross-linked Lyz crystals (CLLC) are among the proteins and templates used in the bioinspired synthesis of subnanometer-sized gold nanoclusters (AuNCs) utilized in various biological applications as biosensors, bioimaging agents, and recyclable catalyst. While previous studies have explored the formation and stabilization of AuNCs in the presence of Lyz, little is known about the enzymatic activity of Lyz after AuNCs stabilization in both its free form (AuNC-Lyz) and within CLLC (AuNC-CLLC). In this study, we conducted a comprehensive analysis of AuNC-Lyz, including hydrodynamic characteristics, using multiwavelength fluorescence analytical ultracentrifugation and enzymatic activity assays. Results show that AuNC-Lyz retains bactericidal performance at pH 4.0 and exhibits enhanced hydrolytic activity compared with Lyz alone. Additionally, AuNC-Lyz showed peroxidase-like performance due to the catalytically active surface of AuNCs providing the bifunctional catalytic capabilities of AuNC-Lyz. In contrast, fluorescent-based hydrolytic activity assays of AuNC-CLLC revealed that morphological variations in CLLC affect the catalytic performance. The AuNC-CLLC enzyme activity depends on the size of the solvent channels and Lyz conformation within CLLC. As a consequence of the occluded solvent channels and limited breathing (in/out diffusion) of CLLC, AuNC-CLLC displayed a diminishing hydrolytic performance.
CRIS-Team Scopus Importer:2024-11-08
Keywords: bactericidal activity; cross-linked lysozyme crystals; fluorescent gold nanoclusters; lysozyme; mimic peroxidase

Influence of group-velocity dispersion on multilevel phase-preserving amplitude regeneration in a nonlinear amplifying loop mirror - Röthlingshöfer, Tobias; Toth, Daniel; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
Numerical simulations have shown a significant influence of group-velocity dispersion (GVD) of the highly nonlinear fiber on the transfer characteristics of a nonlinear amplifying loop mirror (NALM). The effect is especially strong for the anomalous dispersion regime where an interaction of GVD and self-phase modulation (SPM) leads to formation of high-order solitons. The irregularities of the resulting NALM transfer functions can be used for phase-preserving amplitude regeneration of several, irregular-spaced amplitude states for multi-level modulation formats. The regeneration performance was estimated for a 16QAM signal with three amplitude states where a reduction of amplitude noise without significant signal phase distortions has been observe
lhft_intern.bib::Roethlingshoefer2012ca

Influence of Group Velocity Dispersion on phase-preserving Amplitude Regeneration by a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Lasers and Electro-Optics, 2008 and Conference on Quantum Electronics and Laser Science, pages 1-2, 4 - 8 May, 2008)
The influence of dispersion of the highly nonlinear fiber in the loop of a nonlinear amplifying loop mirror on its performance as a 2R regenerator for phase-encoded optical signals has been studied. © 2008 Optical Society of Americ
UnivIS-Import:2017-12-18:Pub.2008.tech.IE.LEH.influe

Interacting waves on chains of split-ring resonators in the presence of retardation - Lomanets, Vadym; Zhuromskyy, Oleksandr; Onishchukov, Georgy; Sydoruk, Oleksiy; Tatartschuk, Eugen; Shamonina, E.; Leuchs, Gerd; Peschel, Ulf (Applied Physics Letters, 2010)
Wave propagation is studied experimentally in a one-dimensional periodic chain of magnetically coupled split-ring resonators with a spacing of about one tenth of the resonant wavelength. Retardation leads to a strong interaction between magnetoinductive and free-space waves. Two kinds of guided modes are observed: a slow backward wave which propagates far outside the light cone, and a fast forward wave close to the light cone. The two merge in a region of zero group velocity. The results are relevant for all one- and two-dimensional periodic systems interacting with waves of the surrounding space.
EAM Import::2019-03-13

Multilevel amplitude and phase regeneration in a nonlinear amplifying loop mirror with a phase-sensitive amplifier - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
A novel regenerator scheme for all-optical multilevel simultaneous amplitude and phase noise suppression is proposed. For a star-8QAM signal, consisting of two amplitude and four phase states, EVM reduction is 4 dB and 2.5 dB for the high- and low-power states, respectively. The limiting effects of the regenerator performance have been considered.
lhft_intern.bib::Roethlingshoefer2012cb

Multilevel Phase-Preserving Amplitude Regeneration Using a Single Nonlinear Amplifying Loop Mirror - Hierold, Martin; Roethlingshoefer, Tobias; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2011)
lhft_intern.bib::Hierold2011

Nonlinear Phase Noise Reduction in a DPSK Transmission System Using Cascaded Nonlinear Amplifying Loop Mirrors - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2009)
The performance of a nonlinear amplifying loop mirror as a phase-preserving amplitude 2R regenerator in a differential phase-shift-keying transmission system with nonlinear phase noise as dominant limiting effect has been investigated in a recirculating fiber-loop setup. The experimental results show that cascaded regenerators can efficiently prevent the accumulation of nonlinear phase noise in such systems. It was possible to significantly increase the transmission quality; alternatively, a considerable increase of fiber launch power could be achieved for the same bitor ratio. As a limiting effect, the amplified Rayleigh backscattering in the highly nonlinear fiber is identified when the regenerator is passed multiple times. © 2009 IEEE.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.nonlin
Keywords: 2r regeneration; Differential phase-shift keying (DPSK); Nonlinear amplifying loop mirror (NALM); Nonlinear phase noise

Nonlinear Phase-Shift Compensation by a Nonlinear Amplifying Loop Mirror - Schmauß, Bernhard; Sponsel, Klaus; Stephan, C.; Onishchukov, Georgy; Leuchs, Gerd (Conference on Lasers and Electro-Optics CLEO, Paper JThE59, San Jose, May, 2010)
The nonlinear amplifying loop mirror as a nonlinear phase-shift compensator for multilevel phase-encoded optical signals is considered. Simulations of a 20 Gb/s DQPSK transmission system showed a significant BER improvement for post-compensation.
lhft_intern.bib::Schmauss10a

Optical diametric drive acceleration through action–reaction symmetry breaking - Wimmer, Martin; Regensburger, Alois; Bersch, Christoph; Miri, Mohammad-Ali; Batz, Sascha; Onishchukov, Georgy; Christodoulides, Demetrios N.; Peschel, Ulf (Nature Physics, 2013)
Newton's third law of motion is one of the pillars of classical physics. This fundamental principle states that the forces two bodies exert on each other are equal and opposite. Had the resulting accelerations been oriented in the same direction, this would have instead led to a counterintuitive phenomenon, that of diametric drive. In such a hypothetical arrangement, two interacting particles constantly accelerate each other in the same direction through a violation of the action–reaction symmetry. Although in classical mechanics any realization of this process requires one of the two particles to have a negative mass and hence is strictly forbidden, it could nevertheless be feasible in periodic structures where the effective mass can also attain a negative sign. Here we report the first experimental observation of such diametric drive acceleration for pulses propagating in a nonlinear optical mesh lattice. The demonstrated reversal of action–reaction symmetry could enable altogether new possibilities for frequency conversion and pulse-steering applications.
EAM Import::2019-03-08

Optical Gap solitons and Truncated Nonlinear Bloch Waves in Temporal Lattices - Bersch, Christoph; Onishchukov, Georgy; Peschel, Ulf (Physical Review Letters, 2012)
We experimentally demonstrate the formation and stable propagation of various types of discrete temporal solitons in an optical fiber system. Pulses interacting with a time-periodic potential and defocusing nonlinearity are shown to form gap solitons and nonlinear truncated Bloch waves. Multi-pulse solitons with defects, as well as novel structures composed of a strong soliton riding on a weaker truncated nonlinear Bloch wave are shown to propagate over up to eleven coupling lengths. The nonlinear dynamics of all pulse structures is monitored over the full propagation distance which provides detailed insight into the soliton dynamics.
EAM Import::2019-03-08

Optical Transient Suppression using Stimulated Raman Attenuation - Holtmannspötter, Michael; Stephan, C.; Onishchukov, Georgy; Leuchs, Gerd; Schmauß, Bernhard (ECOC, September, 2008)
Dynamic optical attenuation based on the Raman Effect is investigated experimentally. The suppression of optical power transients as they arise from dynamic processes of EDFAs is shown. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.optica_3

Optimization of a nonlinear amplifying loop mirror for amplitude regeneration in phase-shift-keyed transmission - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2007)
We present the numerical optimization of the transmission characteristics of a nonlinear amplifying loop mirror for amplitude regeneration of phase-encoded optical transmission formats. Adjusting the splitting factor, the amplifier gain and the phase bias, minimal phase distortions can be achieved while strong amplitude fluctuations are regenerated. The limiting effects of noise from the built-in amplifier and of amplified Rayleigh backscattering are also discussed. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.optimi
Keywords: 2R-regeneration; All-optical regeneration; Differential phase-shift keying; Nonlinear amplifying loop mirror

Optimization of Dispersion-Imbalanced Loop Mirror for Phase-Preserving Amplitude Regeneration - Röthlingshöfer, Tobias; Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE/LEOS Winter Topicals Meeting Series, 2009)
The adaptation and optimization of a dispersionimbalance loop mirror for phase-preserving amplitude 2R regeneration is shown by numerical simulations. Its performance has been evaluated for DPSK transmission. A 4.8dB Q-factor improvement has been demonstrated.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.optimi

Parity-time synthetic photonic lattices - Regensburger, Alois; Bersch, Christoph; Miri, Mohammad-Ali; Onishchukov, Georgy; Christodoulides, Demetrios N.; Peschel, Ulf (Nature, 2012)
The development of new artificial structures and materials is today one of the major research challenges in optics. In most studies so far, the design of such structures has been based on the judicious manipulation of their refractive index properties. Recently, the prospect of simultaneously using gain and loss was suggested as a new way of achieving optical behaviour that is at present unattainable with standard arrangements. What facilitated these quests is the recently developed notion of `parity–time symmetry' in optical systems, which allows a controlled interplay between gain and loss. Here we report the experimental observation of light transport in large-scale temporal lattices that are parity–time symmetric. In addition, we demonstrate that periodic structures respecting this symmetry can act as unidirectional invisible media when operated near their exceptional points. Our experimental results represent a step in the application of concepts from parity–time symmetry to a new generation of multifunctional optical devices and networks.
EAM Import::2019-03-08

Performance analysis of simultaneous multilevel amplitude and phase regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (39th European Conference and Exhibition on Optical Communication (ECOC), 2013)
A star-8QAM regeneration was investigated in numerical simulations for two schemes: a combined NALM with a PSA in the loop and a cascade of PSA and NALM. Significant improvements in error vector magnitude and bit error rate are achieved for both schemes in a transmission system limited by amplified spontaneous emission and nonlinear phase noise.
lhft_intern.bib::Roethlingshoefer2013a

Phase-Preserving 2R-Regeneration of an 80-Gb/s RZ-DQPSK, Signal by Using a Nonlinear Amplifying Loop Mirror - Cvecek, Kristian; Sponsel, Klaus; Stephan, Christian; Ludwig, R.; Schubert, Christina; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (ECOC September, 2007)
The performance of a nonlinear amplifying loop mirror as a 2R regenerator for an 80-Gb/s RZ-DQPSK has been investigated. A significant eye-opening improvement and a negative power penalty of 2.6 dB have been obtained.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.phasep

Phase-Preserving 2R-Regeneration of a WDM RZ-DPSK Signal Using a Nonlinear Amplifying Loop Mirror - Cvecek, Kristian; Sponsel, Klaus; Stephan, C.; Onishchukov, Georgy; Ludwig, R.; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (Optical Communication / National Fiber Optic Engineers Conference OFC/NFOEC 24.-28.02., 2008)
A modified NALM setup for phase-preserving amplitude regeneration of WDM-DPSK signals is proposed. Demultiplexing-multiplexing within the NALM fiber loop is used to avoid WDM channel crosstalk, A negative power penalty of 1.2 dB was obtained. © 2007 Optical Society of America.
UnivIS-Import:2017-11-07:Pub.2008.tech.IE.LEH.phasep

Phase-preserving amplitude regeneration for a WDM RZ-DPSK signal using a nonlinear amplifying loop mirror - Onishchukov, Georgy; Cvecek, Kristian; Sponsel, Klaus; Stephan, Christian; Ludwig, R.; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2008)
We propose a modified nonlinear amplifying loop mirror (NALM) for phase-preserving 2R regeneration of wavelength division multiplexed (WDM) return-to-zero differential phase-shift-keyed signals. As proof of principle the regeneration capability of this NALM setup has been investigated experimentally for two 10 Gbit/s wavelength channels. A significant eye-opening improvement and a negative power penalty of 1.2 dB have been observed in both channels. © 2008 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.phasep

Phase-Preserving Amplitude Regeneration in DPSK Transmission Systems Using a Nonlinear Amplifying Loop Mirror - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Journal of Quantum Electronics, 2009)
A phase-preserving 2R regenerator based on a nonlinear amplifying loop mirror was implemented in a RZ-DPSK transmission system. Its performance has been investigated in numerical simulations and experimentally. The results show that amplitude regeneration using a NALM can efficiently prevent accumulation of nonlinear phase noise in a 10 Gb/s DPSK transmission system. In the experiments, significant improvements of eye opening and of BER as well as a 3 dB increase in fiber launch power have been demonstrated. Simulations at 10 Gb/s and 100 Gb/s indicated that the enhancement of the transmission quality is smaller at 100 Gb/s. The reason is that at 100 Gb/s nonlinear intra-channel effects rather than pure nonlinear phase noise are the main limiting factor and the NALM can only reduce the accumulation of amplitude noise in that case. © 2009 IEEE.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.phasep
Keywords: 2R regeneration; Differential phase-shift keying; Nonlinear amplifying loop mirror; Nonlinear phase noise

Phase-Preserving Amplitude Regeneration Using Dispersion-Imbalanced Loop Mirror - Röthlingshöfer, Tobias; Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Fiber Communication 2009, 2009)
Scheme and parameters of dispersion-imbalance loop mirror (DILM) have been optimized for phase-preserving amplitude 2R regeneration. DILM performance for DPSK transmission has been evaluated in numerical simulations. A 4.8 dB Q-factor improvement has been demonstrated. © 2009 OSA.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.phasep
Keywords: (060.4370) Nonlinear optics; fibers; (060.5060) Phase modulation

Phase-Preserving Signal Regeneration by a Nonlinear Amplifying Loop Mirror - Sponsel, Klaus; Cvecek, Kristian; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Cleo Juni, 2007)
This work presents the numerical investigations on the physical limitations and optimization of the nonlinear amplifying loop mirror (NALM) as a regenerator of phase-shift-keyed signals. The NALM consists of a bidirectional amplifier and a highly nonlinear fiber (HNLF), combined to a loop by a fiber coupler. The transfer functions for the NALM versus dispersion for an amplifier gain for anomalous and normal dispersion were studied. It should be mentioned that beside the nonlinear chirp, the NALM also causes spectral broadening and pulse shape distortions. Amplified spontaneous emission from the NALM amplifier is comparably lower and therefore negligible as a source of optical signal-to-noise ratio (OSNR) penalty.
UnivIS-Import:2017-12-18:Pub.2007.tech.IE.LEH.phasep_0

Phase regeneration of a star-8QAM signal in a phase-sensitive amplifier with conjugated pumps - Stiller, Birgit; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
We demonstrate numerically phase regeneration of a star-8QAM signal with two amplitude and four phase states in a phase-sensitive amplifier. In a dual-stage setup, two phase-conjugated idlers are generated in a first stage consisting of two fiber-optic parametric phase-insensitive amplifiers operated in highly nonlinear gain regime. These are used as pumps in the second, phase-sensitive amplification stage which enables efficient phase regeneration via a degenerate four-wave-mixing process. The latter can be operated in two different operation modes: without format conversion or with phase-shifted amplitude levels. In both regimes, we observe high phase-regeneration efficiency for all amplitude levels: the initial phase noise with 0.2 rad standard deviation is reduced by a factor of 5.
lhft_intern.bib::Stiller2014

Photon Propagation in a Discrete Fiber Network: An Interplay of Coherence and Losses - Regensburger, Alois; Bersch, Christoph; Hinrichs, Benjamin; Onishchukov, Georgy; Schreiber, Andreas; Silberhorn, Christine; Peschel, Ulf (Physical Review Letters, 2011)
We study light propagation in a photonic system that shows stepwise evolution in a discretized environment. It resembles a discrete-time version of photonic waveguide arrays or quantum walks. By introducing controlled photon losses to our experimental setup, we observe unexpected effects like subexponential energy decay and formation of complex fractal patterns. This demonstrates that the interplay of linear losses, discreteness and energy gradients leads to genuinely new coherent phenomena in classical and quantum optical experiments. Moreover, the influence of decoherence is investigated.
EAM Import::2019-03-12

Quantitative Optical and Structural Comparison of 3D and (2+1)D Colloidal Photonic Crystals - Römling, Lukas; Bleyer, Gudrun; Görlitzer, Eric; Onishchukov, Georgy; Vogel, Nicolas (Langmuir, 2023)
Colloidal crystals are excellent model systems to study self-assembly and structural coloration because their periodicities coincide with the wavelength range of visible light. Different assembly methods inherently introduce characteristic defects and irregularities, even with nearly monodisperse colloidal particles. Here, we investigate how these imperfections influence the structural coloration by comparing two techniques to obtain colloidal crystals. 3D colloidal crystals produced by convective assembly are well-ordered and periodically arranged but show microscopic cracks. (2+1)D colloidal crystals fabricated by stacking individual monolayers show a decreased hexagonal order and limited crystal registration between single monolayers in the z-direction. We investigate the optical properties of both systems by comparing identical numbers of layers using correlative microspectroscopy. These measurements show that the less ordered (2+1)D colloidal crystals exhibit higher reflected light intensities. Macroscopic reflection integrating all angles shows that the reflected light intensity levels out with an increasing number of layers, whereas incoherent scattering increases. Although both types of colloidal crystal show similar angle-dependent color shifts in specular reflection, the less-ordered structure of the (2+1)D colloidal crystal scatters light within a larger angular range under diffusive illumination. Our results suggest that structural coloration is surprisingly robust toward local defects and irregularities.
CRIS-Team Scopus Importer:2023-04-14

Reduction of Nonlinear Phase Noise in DPSK Transmission Using a NALM - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE/LEOS Winter Topicals Meeting Series, 2009)
Performance of a NALM as phase-preserving amplitude 2R-regenerator in a DPSK transmission system has been investigated experimentally and numerically. A 3dB improvement of eye opening or alternatively a 3dB increase of fibre-launched power are demonstrated.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.reduct

Reduction of the Rayleigh-Backscattering Impact in Nonlinear Loop Mirrors by Dispersion Management - Röthlingshöfer, Tobias; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (OSA Conference on Nonlinear Photonic, 2010)
UnivIS-Import:2016-06-01:Pub.2011.tech.IE.LEH.reduct

Suppression of Nonlinear Phase Noise in a DPSK Transmission Using a Nonlinear Amplifying Loop Mirror - Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Fiber Communication 2009, 2009)
Experimental and numerical investigations of phase-preserving amplitude regeneration in a DPSK transmission with a NALM have shown that a 3dB improvement of the Q-factor or alternatively a 3dB increase of fiber-launched power could be achieved. © 2009 IEEE.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.suppre

Use of Fiber Nonlinearities for Signal Improvement in Optical Transmission Systems - Schmauß, Bernhard; Holtmannspötter, Michael; Stephan, Christian; Sponsel, Klaus; Onishchukov, Georgy; Leuchs, Gerd (Frequenz, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.useoff

Using saturation effects in a nonlinear amplifying loop mirror for multilevel phase-preserving amplitude regeneration - Roethlingshoefer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2011 13th International Conference on, 2011)
The influence of amplifier gain saturation in nonlinear amplifying loop mirror on simultaneous phase-preserving regeneration of two power states has been studied. Numeri cal simulations have shown an improvement of up to 4 dB for the first, low-power state and 8 dB for the se cond high-power state. Compar ed to the linear amplifier case an improvement of 3 dB for the se cond power state has been achieved.
lhft_intern.bib::Roethlingshoefer2011a
Keywords: 2R regeneration; quadrature amplitude modulation; NALM; NOLM